A history of European integration since 1914 - Stirk, Peter M. R., 1954- (New York : Pinter, 1996)
The First World War, like the Second, was to have a profound impact upon the development of European integration. However, the First World War also ushered in a period of violent instability which dramatically shaped the form of integration in Europe. It is the central contention of this book that the integration process can only be understood and assessed in the light of this instability. In this broad-ranging, chronological study, the author charts the development of European integration since 1914, from Pan-Europa to the relative uncertainty of the post-Cold War period. The volume will be of interest to students, academics and researchers.
Ch. 1. Pre-1914 Origins -- Ch. 2. Between Pan-Europa and Mitteleuropa: 1914-39 -- Ch. 3. Making the New Europe in the Second World War: 1940-45 -- Ch. 4. The Reconstruction of Europe under Superpower Hegemony: 1945-49 -- Ch. 5. The Years of Growth and the Foundation of the Communities: 1950-60 -- Ch. 6. The Development and Limits of Integration in the 1960s and 1970s -- Ch. 7. The Triumph of the European Community? -- Ch. 8. The New European Architecture.
Includes bibliographical references and index.
Keywords: European federation -- History; Europe -- Economic integration -- History